Pengaruh Ekstrak Bunga Rosella (Hibiscus Sabdariffa L.) Terhadap Kekuatan Rekat Geser Resin Komposit pada Gigi Pasca Bleaching - Rizky Amenta Tarigan; Maya Hudiyati; Mellani Cindera Negara (Jurnal Material Kedokteran Gigi, 2014)
Bleaching is a dental procedure to repair tooth discoloration by using chemical agents such as 35% hydrogen peroxide. The bleaching agents may cause a side effect, such as a decrease in shear bond strength of composite resin. This can be overcome with the use of antioxidants such as 10% sodium ascorbate which can reduce residual oxygen from the bleaching agents. Antioxidants are also found in a rosella flower (Hibiscus sabdariffa L.). The purpose of this study was to evaluate the effect of rosella flower extract on shear bond strength of composite resin to bleached teeth. A 35% hydrogen peroxide was applied to thirty premolar teeth. The teeth were divided into three groups: group I (without an antioxidant), group II (using 10% sodium ascorbate), and group III (using rosella flower extract); then a composite resin was applied on the teeth surfaces. The shear bond strength was measured by Universal Testing Machine. The data were analyzed by one way ANOVA and post-hoc LSD. The mean of shear bond strength (MPa) for group I was 17.74±1.49, group II was 23.25±1.64, and group III was 19.31±1.01. The results of stastitical tests showed significant differences among the groups (p<0.05). The conclusion of this study is the rosella flower extract increased the shear bond strength of composite resin to bleached teeth, however it showed lower shear bond strength compared to 10% sodium ascorbate.